Variations of Coconut Shell, Rice Husk, and Bagasse as an Alternative of Briquettes Materials - Sari, Kartika; Anisyah, Anisyah; Toruan, Parmin Lumban; Setiawan, Andi Arif (Jurnal ILMU DASAR, 2024)
The current energy condition is getting thinner meanwhile people's daily lives still use a lot of energy derived from fossil fuels so that its use is increasing with limited availability. An alternative to reduce the use of fossil energy is by utilizing waste biomass as an energy source one of them is briquetts. This study aims to analyze the characteristics of briquettes from a variety of briquette mixtures made from coconut shells, rice husks, and bagasse. The method used is survey and experimental. The survey of sampling coconut shells was carried out in the Seberang Ulu I area, rice husks in the Pegayut area, and bagasse was obtained at the ice cane traders in the Seberang Ulu I area. The data obtained were presented in graphical form and analyzed descriptively. The results obtained are the water content in the variation of the combination of briquette-making materials ranging from 4.23 - 5.13%, ash content of 7.6 - 7.86%, the density value obtained is 0.55 - 0.59 g/cm3, the compressive strength value is 25.67 - 37.33 kg/cm2, and the calorific value is 4756 - 4865 cal/gr. The results showed there is not significant differences in moisture content, ash content, and compressive strength, while the density and calorific value showed significant differences.